Cyclic Voltammetry Study of the Influence of Concentration of K3[Fe(CN)6] and Glucose on Glassy Carbon Electrode - Adella Fajaretta Gunawan; Arie Hardian; Anceu Murniati (UNIVERSITAS SEBELAS MARET (UNS), 2025)
Biosensors are cost-effective, user-friendly devices with rapid response, sensitivity, selectivity, and stability. This study investigated the impact of K3[Fe(CN)6] concentration and glucose on glassy carbon electrode (GCE) performance. The cyclic voltammetry method determined the effects of varying K3[Fe(CN)6] and glucose concentrations on GCE. GCE characterization utilized K3[Fe(CN)6] solutions (1 – 5 mM) in 0.2 M KCl and achieved an optimum scan rate of 75 mV/s within -1.5 to 1 V vs. Ag/AgCl. Reversible Fe2+/Fe3+ redox occurred at 1mM (ipa/ipc= 0.99), with the highest reduction peak at 5mM. Glucose tests (1mM to 5mM) in 0.1 M NaOH exhibited an optimal scan rate of 200 mV/s within a potential range of -10 – 10 V at 1 mM (ipa/ipc= 1.01), with the highest oxidation peak at 5 mM. GCE effectively measured concentration effects, with ipa/ipc values close to 1, indicating reversible redox processes at low concentrations. Higher concentrations yielded stronger peak currents due to increased electroactive species.